Genetic characterization of LEP and TG5 gene polymorphisms in crossbred beef cattle populations (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: This study aimed to investigate the single nucleotide polymorphisms (SNPs) in the intron 2 region of the leptin (LEP) gene and the 5’ untranslated region of the thyroglobulin (TG5) gene acrossfour crossbred beef cattle populations, including Blanc Bleu Belge × Lai Brahman (BLB), Charolais × Lai Brahman (CLB), Droughtmaster × Lai Brahman (DLB), and Red Angus × Lai Brahman (RLB) raised in Central Vietnam. Materials and Methods: A total of 200 tail hair root samples (50 per group) were collected, and genomic DNA was extracted. The PCR-RFLP method was utilized to analyze the LEP and TG5 gene polymorphisms using the restriction enzymes Sau3AI and PsuI, respectively. Results: The SNPs of LEP/Sau3AI and TG5/PsuI were present in all populations, with a lower frequency of the LEPB allele compared to LEPA. The LEPAA genotype was most common, followed by LEPAB and LEPBB; notably, the LEPBB genotype was absent in the CLB group. The Hardy–Weinberg equilibrium was observed for LEP/Sau3AI in the CLB and BLB populations. Conversely, the TG5CT genotype dominated all groups, with no individuals exhibiting the TG5TT genotype. None of the populations achieved Hardy–Weinberg equilibrium for TG5/PsuI. The level of polymorphism was moderate for LEP/Sau3AI in RLB and BLB and for TG5/PsuI across all groups. Conclusion: The SNPs of LEP/Sau3AI and TG5/PsuI may serve as valuable tools for genomic selection. By focusing on increasing the frequency of the TG5T allele, breeding programs can more effectively enhance beef marbling and other important traits, leading to improved beef quality and greater economic outcomes in the cattle industry.J. Adv. Vet. Anim. Res., 11(4): 989–995, December 2024http://doi.org/10.5455/javar.2024.k849